Analysis of Students’ Mathematical Problem-Solving Ability Reviewed from Systematic and Intuitive Cognitive Styles - Neng Yulianti; Linda Herawati; Yeni Heryani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study aims to describe students’ mathematical problem-solving abilities based on systematic and intuitive cognitive styles using a qualitative descriptive approach. The participants consisted of four seventh-grade students of Class VIIB at SMP Negeri 21 Tasikmalaya, including two students with a systematic cognitive style and two students with an intuitive cognitive style, selected through purposive sampling based on the results of the Cognitive Style Inventory (CSI) questionnaire. Data were collected through questionnaires, mathematical problem-solving tests based on Polya’s stages, and interviews, then analyzed through data reduction, data display, and conclusion drawing. The findings showed that students with a systematic cognitive style tended to solve problems in a structured, sequential, and careful manner, whereas students with an intuitive cognitive style tended to solve problems more quickly and spontaneously by relying on direct understanding and prior experience in determining solution strategies.These findings indicate that cognitive style plays an important role in shaping how students interpret problems, select strategies, and evaluate solutions in mathematical problem-solving.